PENGARUH WAKTU FERMENTASI DAN PERSENTASE STARTER PADA NIRA AREN (Arenga pinnata) TERHADAP BIOETHANOL YANG DIHASILKAN - Isna Syauqiah (INFO-TEKNIK, 2015)
Bioethanol can be produced from the fermentation of sugar-containing materials such as cassava, corn and sugar palm juice.  This study aims to determine the effect of fermentation using Saccharomyces sp at various percentages starter towards substrate ability to produce bioethanol. Variation of fermentation time used are 25, 50 and 75 hours. Keywords: Bioethanol, fermentation, sugar palm juice, Saccharomyces cerevisiae